2016
DOI: 10.14687/ijhs.v13i1.3670
|View full text |Cite
|
Sign up to set email alerts
|

School truancy among Turkish high school students: A test of General Strain Theory

Abstract: School absenteeism is a complicated problem with a variety of causes. It has been shown to be one of the main predictors of school drop-outs as well as leading to delinquency and criminal behavior in adulthood. This study examines the applicability of General Strain Theory on educational factors by considering truancy as a risk behavior. In this empirical study, we test the explanatory powers of certain kinds of strain, including school strain, economic deprivation, negative life events, anger, college plans, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
2
0
1
Order By: Relevance
“…The results of the series of statistical analyses generally support our hypotheses, with a few exceptions. Specifically, supporting our first hypothesis, the binary logistic regression results demonstrated that unit strain, negative life experiences, and physical victimization were all associated with an increase in the likelihood of engaging in criminal offending, drug use, and heavy alcohol use, findings that also confirm those of previous research conducted on civilian samples and validate these findings in a military context (Arter, 2008; Aseltine et al, 2000; Orak & Solakoglu, 2017; Slocum, 2010; Solakoglu & Orak, 2016).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results of the series of statistical analyses generally support our hypotheses, with a few exceptions. Specifically, supporting our first hypothesis, the binary logistic regression results demonstrated that unit strain, negative life experiences, and physical victimization were all associated with an increase in the likelihood of engaging in criminal offending, drug use, and heavy alcohol use, findings that also confirm those of previous research conducted on civilian samples and validate these findings in a military context (Arter, 2008; Aseltine et al, 2000; Orak & Solakoglu, 2017; Slocum, 2010; Solakoglu & Orak, 2016).…”
Section: Discussionsupporting
confidence: 86%
“…Research has shown that military personnel are subjected to a variety of stressors intrinsic to military organizations such as difficult and dangerous duties, negative unit experiences, physical exhaustion, blockage of career goals, exposure to traumatic events, negative combat experiences, and long deployment periods (Grinker & Spiegel, 1945;Hoge et al, 2004;Mitchell et al, 2011;Pflanz, 1999). It is also well-established that there is a strong correlation between stress and deviant behavior (Arter, 2008;Aseltine et al, 2000;Orak & Solakoglu, 2017;Slocum, 2010;Solakoglu & Orak, 2016). Yet the extant research has generally failed to address the mechanisms by which stressful experiences among military service-members lead to deviant reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Absenteeism is an undesirable behaviour because in long term, absenteeism can make students disadvantaged to be a productive person, and the tendency of students who have the habit of not attending school may increase (Önder, 2017, p. 362). It has been frequently mentioned in previous studies (ERG, 2015;MEB, 2015MEB, , 2016MEB, , 2018MEB, , 2019OECD, 2014;Solakoğlu, & Orak, 2016;TEDMEM, 2019, p. 7) that there are important problems related to school absenteeism in Turkish education system. To prevent student absenteeism, the reasons for absenteeism should be determined firstly.…”
Section: Extended Abstractmentioning
confidence: 95%
“…Türk eğitim sisteminde okula devamsızlık ile ilgili önemli sorunlar olduğu daha önce yapılan çalışmalarda da (ERG, 2015;MEB, 2015MEB, , 2016MEB, , 2018MEB, , 2019OECD, 2014;Solakoğlu ve Orak, 2016;TEDMEM, 2019, s. 7) sık sık dile getirilmiştir. Örneğin, e-okul verilerinin kullanıldığı bir çalışmaya göre, Türkiye'de 10 gün ve üstü devamsızlık oranları oldukça yüksektir (ERG, 2015).…”
Section: Introductionunclassified